Clients\' perception toward quality of postnatal care in the Gaza Strip, Palestine: A direction for health policy change" - Areefa SM Alkasseh; Samar Mwaafy; Nasser Abu-El-Noor; Mysoon Abu-El-Noor (Journal of Holistic Nursing and Midwifery)
Introduction: Most maternal and neonatal deaths occur during the postnatal period. Therefore, the quality of care provided by healthcare professionals at this critical time is crucial in reducing complications, morbidity, and mortality rates. Objective: The present study aimed to determine the perceptions of Palestinian women living in the Gaza Strip considering the quality of care they received in the early postpartum period. Materials and Methods: An analytical cross-sectional study was conducted using a self administered questionnaire developed by the researchers. A total of 200 pregnant women were selected by convenience sampling method from 4 governmental hospitals in the Gaza Strip, Palestine providing postnatal care. Descriptive statistics, including frequency, mean, and standard deviations, were used to describe the variables. Analysis of Variance (ANOVA) and Independent Samples t-test was used to compare the collected mean scores. Results: The study participants rated the postnatal services they received as high-quality care. High mean scores were achieved for all study domains. The “quality of postnatal care provided by midwives” received the highest Mean±SD score of 4.16±0.60, followed by the domain “quality of postnatal baby care” with a Mean±SD score of 3.89±0.85. The other two domains of “quality of provided health education” and “quality of provided communication and psychological support” received the lowest mean scores of 3.81 with standard deviations of 0.90 and 0.80, respectively. Patient-perceived postnatal care quality was not affected by many variables, such as age, parity, and gravidity. It was only affected by the subjects’ level of education (P=0.001) and the place of delivery (P=0.017). Conclusion: The obtained results posed a challenge for healthcare policymakers and professionals working in maternity departments. A new policy and leadership directions are required in this critical and vulnerable clinical area. To improve the quality of postnatal care, health policymakers must collaborate with midwifery staff. It is important to identify and eliminate any barriers that impede the provision of better care. This will be reflected by reducing maternal and neonatal morbidity and mortality rates and reducing the number of hospitalization days.